Rearrange the equation of the line into slopeintercept form: y = mx + b ,
where m is the slope of the line and b is the yintercept (the yintercept is the point where x= 0).
6x + 2y = 12 subtract 6x from both sides of the equation
2y = 6x + 12 divide both sides of the equation by 2
y = 3x + 6 ==> yintercept (b):
y = 6
Conversely, the xintercept is the point where y = 0:
y = 3x + 6
0 = 3x + 6 add 3x to both sides of the equation
3x = 6 divide both sides of the equation by 3
x = 2 ==> xintercept
The slopeintercept form of the line given by the equation 9x + 5y = 4 is as follows:
5y = 9x + 4 after subtracting 9x from both sides of the equation, divide both sides by 5
y = (9/5)x + (4/5)
The yintercept here is given by b; thus, y = 4/5.
Solving for x when y = 0 yields the xintercept:
0 = (9/5)x + (4/5)
(9/5)x = (4/5)
(5/9)(9/5)x = (4/5)(5/9)
x = 4/9 ==> xintercept
3/18/2013

Tamara J.